Pelaksanaan Pembelajaran Biologi Kurikulum Berbasis Cinta pada SMK Kesehatan Athallah - Anggi Suko Wati; Ahmad Zainuri; Arni Arni (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This study describes the implementation of Biology learning based on the Love-Based Curriculum (KBC) at SMK Kesehatan Athallah. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation during August–September 2025. Data analysis followed the Miles and Huberman model. The results indicate that the learning process was carried out in three stages: an introduction emphasizing spirituality, core activities using Problem Based Learning (PBL), and a closing session through joint reflection. A contextual teaching module integrating values of love, empathy, responsibility, and environmental care motivated more than 83% of students and fostered positive behavioral changes, including discipline, environmental awareness, and mutual respect. The main challenges were the limited contextualization of the teaching module and the need for continuous teacher training. In conclusion, the implementation of KBC enhanced students’ motivation, conceptual understanding, and empathy, making it relevant for vocational education in the health sector.